A method for surface strengthening of a last stage blade of a steam turbine

CN122979894APending Publication Date: 2026-10-27XINJIANG TIANCHI THERMOELECTRICITY CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611227612.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该工艺存在两个突出问题:一是异种金属钎焊界面存在冶金缺陷风险,在交变载荷下易产生裂纹;二是Stellite合金与基体材料的力学性能差异较大,热膨胀系数不匹配导致界面残余应力

Benefits of technology

经本发明强化的不锈钢叶片表面硬度提高到500HBW以上,达到基材的2倍以上,显著提高叶片的耐磨性,强化层厚度为1~2mm可满足使用需求;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979894A_ABST
    Figure CN122979894A_ABST
Patent Text Reader

Abstract

The application discloses a surface strengthening method for a last-stage blade of a steam turbine, and the method comprises the following steps: preparing a metal coating with uniform thickness on the surface of a pretreated blade blank by using a multi-arc ion plating device; remelting the surface of the blade blank with the metal coating by using an automatic powder feeding laser cladding device, and introducing graphite powder; and obtaining a multi-scale hard particle reinforced layer on the surface of the blade. The surface hardness of the blade is increased to more than 500 HBW, which is more than twice of the base material, the wear resistance of the blade is significantly improved, and the thickness of the reinforced layer is 1-2 mm, which can meet the use requirement. The multi-scale carbide and the solid solution reinforced layer have a good bonding interface with the base material, and the stability of the blade under different working conditions is improved. Through the synergy of the nano-micro multi-scale particles, the hardness is improved, and the water erosion impact resistance and the fatigue resistance of the stainless steel blade are significantly enhanced; the interface of the carbide particles generated in situ is clean and firm, and the consistency of the performance of the reinforced layer is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention patent relates to the field of metal materials and application technology, and in particular to a surface strengthening method for the last stage blades of a steam turbine. Background Technology

[0002] Driven by the "dual carbon" goals, deep peak-shaving operation of coal-fired power units has become the norm. The failure risks of water erosion, fatigue, and flutter faced by the last stage blades of steam turbines have been significantly aggravated, and the existing protection technology of stainless steel materials for blades is difficult to meet the requirements of the new operating conditions.

[0003] Brazing with Stellite alloy is a traditional process for preventing water erosion on blades, improving their resistance to water erosion by brazing Stellite alloy sheets onto the inlet edge of the blade. However, this process has two prominent problems: first, the brazing interface between dissimilar metals carries the risk of metallurgical defects, making it prone to cracking under alternating loads; second, the significant difference in mechanical properties between the Stellite alloy and the base material, along with the mismatch in thermal expansion coefficients, leads to residual stress at the interface. Frequent thermal cycling under deep peak-shaving conditions accelerates interface damage.

[0004] Thermal spray coatings (such as WC-Co and Cr3C2-NiCr) have the advantages of flexible processing and low cost, but the bonding strength between the coating and the substrate is limited (usually 30~70 MPa), and they are prone to peeling under high-speed water droplet impact. In addition, thermal spray coatings have high porosity (usually 1%~5%), and corrosive media can penetrate along the pores to the interface, leading to coating failure.

[0005] Surface hardening (such as high-frequency hardening) can form a hardened layer on the blade surface, improving its resistance to water erosion. However, the depth of the hardened layer is limited (usually 1-2 mm), and there is a risk of deformation. For blades with complex profiles, it is difficult to guarantee the uniformity of hardening.

[0006] As can be seen from the above, there is a need to develop new methods for repairing and modifying the last-stage blades of steam turbines to meet their requirements under deep peak-shaving conditions. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide a surface strengthening method for the last stage blades of a steam turbine. By introducing a transition layer and multi-scale hard particles on its surface, the fatigue strength and water erosion resistance are improved.

[0008] To address the problems in the prior art, this invention discloses a surface strengthening method for the last stage blades of a steam turbine: Pre-treat the surface of the blade blank; A metal coating of uniform thickness was prepared on the surface of the pretreated blade blank using a multi-arc ion plating equipment; An automatic powder-feeding laser cladding equipment is used to remelt the surface of the blade blank that has obtained a metal coating, and graphite powder is introduced. Modulation treatment is performed on the blade surface to obtain a multi-scale hard particle reinforcement layer on the blade surface; Polish the blade surface.

[0009] Furthermore, the pretreatment of the blade blank surface includes: The oxide layer on the surface of the leaf blank was removed with sandpaper and then ultrasonically cleaned in an ethanol solution for 30 minutes.

[0010] Furthermore, the metal used in the multi-arc ion plating is any one or more of Cr, Mo, V, and W, which is dissolved in Fe.

[0011] Furthermore, the multi-arc ion plating parameters range as follows: target current 60~100A, substrate bias voltage -50~-200V, deposition gas pressure 0.5~3.5Pa, and coating time 90~120min.

[0012] Furthermore, the laser remelting process parameters control the laser power, scanning speed, and powder feeding rate, wherein the laser power is 1800~2000W, the scanning speed is 50~100mm / s, the graphite powder used is high-purity graphite powder with a particle size of 30~45μm, and the powder feeding rate is 2~8g / min.

[0013] Furthermore, the modulation process includes: The quenching temperature is 1100~1170℃, oil cooling, high-temperature tempering temperature is 650~750℃, holding for 60min, and air cooling; finally, a stainless steel matrix structure including lath martensite and carbides is obtained, as well as a surface strengthening layer structure mainly composed of multi-scale carbide hard particles.

[0014] Furthermore, the carbide type is any one or more of (FeCr)7C3, TiC, Mo2C, V8C7, and WC.

[0015] Furthermore, the blade surface is polished to a surface roughness of Ra = 0.020.

[0016] The beneficial effects of this invention are as follows: The surface hardness of the stainless steel blade strengthened by this invention is increased to more than 500 HBW, which is more than twice that of the base material, significantly improving the wear resistance of the blade. The thickness of the strengthening layer is 1~2mm, which can meet the application requirements. A strengthening layer was prepared on the surface of stainless steel blades by combining multi-arc ion plating and laser cladding. The multi-scale carbide layer → solid solution strengthening layer → substrate were formed from the outside to the inside. The multi-scale carbide and solid solution strengthening layer had a good bonding interface with the substrate, which improved the stability of the blades under different working conditions. By using nano- to micro-scale multi-scale particles in synergy, the hardness of stainless steel blades is improved while significantly enhancing their resistance to water erosion and fatigue. The carbide particles generated by the in-situ reaction have clean interfaces and strong bonds, ensuring the consistency of the reinforcement layer's performance. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the surface strengthening process for the last stage blades of a steam turbine according to the present invention; Figure 2 A schematic diagram of the cross-sectional SEM morphology of the multi-scale carbide coating on the surface of 2Cr13; Figure 3 This is a schematic diagram of the SEM morphology of the multi-scale hard coating on the surface of 2Cr13. Detailed Implementation

[0018] The present invention will be further described below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and should not be used to limit the scope of protection of the present invention.

[0019] like Figure 1 As shown, the surface strengthening method for the last stage blade of a steam turbine of the present invention improves fatigue strength and water erosion resistance by introducing a transition layer and multi-scale hard particles on its surface.

[0020] This method combines multi-arc ion plating with laser cladding to achieve surface strengthening of the blade. First, a metal coating with controllable thickness is obtained on the surface of the stainless steel blade through multi-arc ion plating; second, the metal coating is remelted by laser cladding, and graphite powder is introduced at the same time; finally, the surface strengthening of the blade is completed by overall tempering heat treatment.

[0021] The aforementioned multi-arc ion-plated metal layers are Cr, Mo, V, W, etc., which can be dissolved in Fe and have a large degree of solubility, and can even form an infinite solid solution.

[0022] The aforementioned laser cladding remelts the coated metal and simultaneously introduces graphite powder, resulting in multi-scale hard particles on the blade surface. Specifically, the remelting precipitates nanoscale hard particles, which directly react in situ to form micron-scale hard particles, collectively forming a multi-scale hard particle reinforcement layer on the surface. Example 1

[0023] This embodiment provides a surface strengthening method for the last-stage blades of a steam turbine, specifically targeting last-stage blades made of 2Cr13 stainless steel, to improve their resistance to water erosion and fatigue strength under deep peak-shaving operation conditions. The specific steps are as follows: Step 1: Blade preparation Select a 2Cr13 stainless steel last-stage blade blank with intact dimensions, and successively polish the surface of the blank using 240-grit, 600-grit, and 1000-grit metallographic sandpaper to remove the oxide layer. Then, place the polished blank in anhydrous ethanol and clean it with an ultrasonic cleaner for 30 minutes to remove surface oil and residual particles. After removal, dry it with cold air for later use.

[0024] Step 2: Multi-arc ion plating of metal coating A multi-arc ion plating apparatus was used to deposit a Cr metal coating on the blade surface after the treatment in step 1. Specific process parameters were: pure Cr target (purity ≥99.9%), target current set to 80A, substrate bias voltage -120V, deposition gas pressure (Ar atmosphere) 2.0Pa, and deposition time 100 minutes. During deposition, the blade substrate maintained coating uniformity through revolution and rotation. Figure 2 As shown, the thickness of the obtained Cr metal coating is about 15-20 μm. The coating is well bonded to the substrate, and Cr and Fe can form an infinite solid solution, providing a compositional basis for subsequent laser cladding and interface metallurgy.

[0025] Step 3: Laser cladding and remelting and introduction of graphite powder An automated powder-feeding laser cladding system was used to laser remelt the Cr coating surface obtained in step 2, while simultaneously introducing high-purity graphite powder (purity ≥99.9%, particle size 30-45μm). The laser cladding process parameters were: laser power 1900W, scanning rate 80mm / s, powder feeding rate 5g / min, and argon gas with a flow rate of 10L / min. The laser beam scanned along the blade profile, causing localized remelting of the coating. Simultaneously, the graphite powder partially dissolved and participated in the reaction at high temperature. During this process, the original Cr in the coating reacted in situ with Fe and carbon elements in the graphite, precipitating nanoscale (5-30nm) (Fe,Cr)7C3 type carbide particles. At the same time, the incompletely dissolved micron-sized graphite particles reacted with the molten metal to form micron-sized (0.5-5μm) hard particles such as Cr23C6 and Cr7C3. Figure 3 As shown, they together constitute a precursor to a reinforcing layer with a multi-scale, hard particle dispersion.

[0026] Step 4: Overall tempering and heat treatment The blades, after laser cladding, underwent quenching and high-temperature tempering. Specifically, the blades were first heated to a quenching temperature of 1130℃, held for 30 minutes, and then oil-cooled (cooling oil temperature 20-40℃). Following this, high-temperature tempering was performed at 700℃ for 60 minutes, and finally air-cooled to room temperature. After heat treatment, the blade matrix structure transformed into fine lath martensite, with dispersed secondary carbides precipitating between the martensite laths, significantly improving the matrix's toughness and strength. Simultaneously, the original metastable phase in the surface strengthening layer further transformed, with multi-scale hard carbide particles (mainly (Fe,Cr)7C3 and Cr23C6) uniformly and dispersedly distributed in the coating, forming a surface multi-scale hard particle strengthening layer with a thickness of approximately 25-35 μm.

[0027] Step 5: Polishing and finishing The blade surface obtained in step 4 was finished using mechanical polishing. Fine-grained diamond polishing paste was used sequentially until the surface roughness reached Ra=0.020μm. The final product was a turbine last-stage blade with a multi-scale hard particle reinforcement layer, exhibiting a smooth surface, free of cracks and pores.

[0028] Performance testing: After treatment in this embodiment, the average hardness of the surface-strengthened layer, as measured by a microhardness tester, was 780 HV0.2, an increase of approximately 144% compared to the untreated substrate (approximately 320 HV0.2). Comparative tests were conducted on a rotating water erosion testing apparatus (test conditions: water velocity 200 m / s, angle of attack 20°, time 10 hours). The mass loss of the treated blade in this embodiment was only 1 / 5 of that of the untreated blade, and no obvious fatigue spalling pits appeared on the surface, demonstrating excellent water erosion resistance and fatigue resistance. Example 2

[0029] This embodiment is basically the same as embodiment 1, except that: In step 2, Mo was used as the metal target for multi-arc ion plating (purity ≥99.9%). The process parameters were adjusted as follows: target current 100A, substrate bias voltage -180V, deposition gas pressure 3.0Pa, and coating time 110 minutes. The resulting Mo metal coating thickness was approximately 18-22μm.

[0030] In step 3, the laser cladding parameters are adjusted to: laser power 2000W, scanning rate 60mm / s, and powder feeding rate 7g / min (graphite powder particle size 30-45μm). During the remelting process, nano-sized Mo2C, micro-sized Mo2C, and Mo23C6 multi-scale hard particles are generated in situ.

[0031] Step 4 involves heat treatment: quenching at 1150℃, oil cooling; tempering at 720℃, holding for 60 min, and air cooling. The final surface-strengthened layer contains multi-scale hard particles mainly composed of Mo2C, Mo23C6, and a small amount of Fe-Mo carbides, with a matrix structure of lath martensite and fine carbides. After treatment, the surface roughness Ra = 0.020 μm, the average hardness of the surface-strengthened layer is 850 HV0.2, and the water erosion resistance is approximately 6 times higher than that of the untreated blade. Example 3

[0032] This embodiment is basically the same as embodiment 1, except that: In step 2, V is used as the target material for multi-arc ion plating. The process parameters are: target current 70A, substrate bias voltage -80V, deposition gas pressure 1.0Pa, and coating time 95 minutes.

[0033] The laser cladding parameters in step 3 are: laser power 1850W, scanning rate 95mm / s, and powder feeding rate 3g / min. This generates in-situ nano-sized V8C7 and micron-sized VC and V8C7 hard particles.

[0034] Step 4 involves quenching and tempering heat treatment: quenching temperature 1110℃, oil cooling; tempering temperature 660℃, holding for 60 min, air cooling. The final product consists of a lath martensite + dispersed carbide matrix with a multi-scale V8C7 / VC particle reinforcement layer on the surface. After treatment, the surface roughness Ra = 0.020 μm, the surface hardness reaches 820 HV0.2, the water erosion resistance is approximately 5 times higher than the untreated blade, and it also has a lower coefficient of friction.

[0035] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for surface strengthening of the last stage blade of a steam turbine, characterized in that: Pre-treat the surface of the blade blank; A metal coating of uniform thickness was prepared on the surface of the pretreated blade blank using a multi-arc ion plating equipment; An automatic powder-feeding laser cladding equipment is used to remelt the surface of the blade blank that has obtained a metal coating, and graphite powder is introduced. Modulation treatment is performed on the blade surface to obtain a multi-scale hard particle reinforcement layer on the blade surface; Polish the blade surface.

2. The surface strengthening method for the last stage blades of a steam turbine according to claim 1, characterized in that: Pretreatment of the blade blank surface includes: The oxide layer on the surface of the leaf blank was removed with sandpaper and then ultrasonically cleaned in an ethanol solution for 30 minutes.

3. The surface strengthening method for the last stage blades of a steam turbine according to claim 1, characterized in that: The metal used in multi-arc ion plating is any one or more of Cr, Mo, V, and W, which is dissolved in Fe.

4. The surface strengthening method for the last stage blades of a steam turbine according to claim 1, characterized in that: The multi-arc ion plating parameters range as follows: target current 60~100A, substrate bias voltage -50~-200V, deposition gas pressure 0.5~3.5Pa, and coating time 90~120min.

5. The surface strengthening method for the last stage blades of a steam turbine according to claim 1, characterized in that: The laser remelting process parameters control the laser power, scanning speed, and powder feeding rate. The laser power is 1800~2000W, the scanning speed is 50~100mm / s, the graphite powder used is high-purity graphite powder with a particle size of 30~45μm, and the powder feeding rate is 2~8g / min.

6. The surface strengthening method for the last stage blades of a steam turbine according to claim 1, characterized in that, Modulation processing includes: The quenching temperature is 1100~1170℃, oil cooling, high-temperature tempering temperature is 650~750℃, holding for 60min, and air cooling; finally, a stainless steel matrix structure including lath martensite and carbides is obtained, as well as a surface strengthening layer structure mainly composed of multi-scale carbide hard particles.

7. The surface strengthening method for the last stage blades of a steam turbine according to claim 6, characterized in that, The carbide types are any one or more of (FeCr)7C3, TiC, Mo2C, V8C7, and WC.

8. The surface strengthening method for the last stage blades of a steam turbine according to claim 1, characterized in that, The blade surface is polished to a surface roughness of Ra = 0.020.